Ex 2.4
Ex 2.4, 1 (ii)
Ex 2.4, 1 (iii) Important You are here
Ex 2.4, 1 (iv)
Ex 2.4, 1 (v)
Ex 2.4, 2 (i)
Ex 2.4, 2 (ii) Important
Ex 2.4, 2 (iii)
Ex 2.4, 3 (i)
Ex 2.4, 3 (ii) Important
Ex 2.4, 3 (iii)
Ex 2.4, 4 (i)
Ex 2.4, 4 (ii)
Ex 2.4, 4 (iii) Important
Ex 2.4, 4 (iv)
Ex 2.4, 4 (v)
Ex 2.4, 4 (vi)
Ex 2.4, 5 (i)
Ex 2.4, 5 (ii) Important
Ex 2.4, 6 (i)
Ex 2.4, 6 (ii)
Ex 2.4, 6 (iii)
Ex 2.4, 6 (iv) Important
Ex 2.4, 7 (i)
Ex 2.4, 7 (ii)
Ex 2.4, 7 (iii) Important
Ex 2.4, 8 (i)
Ex 2.4, 8 (ii)
Ex 2.4, 8 (iii) Important
Ex 2.4, 8 (iv) Important
Ex 2.4, 8 (v)
Ex 2.4, 9 (i)
Ex 2.4, 9 (ii)
Ex 2.4, 10 (i) Important
Ex 2.4, 10 (ii)
Ex 2.4, 11
Ex 2.4,12 Important
Ex 2.4,13
Ex 2.4, 14 (i)
Ex 2.4, 14 (ii) Important
Ex 2.4, 15 (i)
Ex 2.4, 15 (ii) Important
Ex 2.4, 16 (i)
Ex 2.4, 16 (ii) Important
Ex 2.4
Last updated at Dec. 16, 2024 by Teachoo
You saved atleast 2 minutes by viewing the ad-free version of this page. Thank you for being a part of Teachoo Black.
Ex 2.4, 1 Use suitable identities to find the following products: (iii) (3x + 4) (3x - 5) (3x + 4) (3x – 5) = 3 (𝑥+ 4/3) 3(𝑥− 5/3) = (9) (𝑥+ 4/3) (𝑥− 5/3) Using (x + a) (x + b) = x2 + (a + b) x + ab, Where a = 4/3 , b = (−5)/3 = 9 [𝑥2+(4/3+(−5)/3)𝑥+(4/3)(− 5/3)] = 9 [𝑥2 +((4 − 5))/3 𝑥 −20/9] = 9 [𝑥2 − 1/3 𝑥 −20/9] = 9(𝑥2) −9(1/3)𝑥 −9(20/9) = 9x2 – 3x – 20